DHT (Diapers Hydrogel and Tajin) Fertilizer: Liquid Organic Fertilizer for the Growth of Chili Pepper Plants (Capsicum frustencens) - Mochammad Nasrul Hidayat (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The issue of disposable diaper waste is a significant environmental challenge because it is difficult to decompose, taking between 250 and 500 years, and leads to widespread pollution. The rising volume of diaper waste and the suboptimal disposal of rice wash water (air tajin) require innovative solutions. This research offers a novel approach by integrating the water retention capacity of diaper hydrogel with the nutritional benefits of rice wash water into a single Liquid Organic Fertilizer (LOF) formulation. A nutritional hydrogel derived from used diapers can absorb baby urine, which contains ammonia (approximately 60%) and urea (approximately 35%), both of which are essential nutrients for plants. DHT Fertilizer is created by extracting hydrogel from cleaned, used diapers. The hydrogel is heated to 50 °C for 60 minutes, then mixed with 60 mL of rice wash water. This study aims to repurpose these waste materials into